Fundamentalisme Dan Radikalisme Islam Masa Kini (Suatu Tinjauan Kritis dan Menyeluruh) - M. Said Said P.; Akhmad Syahid (Jurnal Ilmiah Islamic Resources, 2022)
The revival of Islamic groups is essentially an effort to struggle to uphold Islamic ideals, as normatively accelerated it is seen as able to provide a certainty of life in the future. The revival of the Islamic religion will raise various questions again regarding the diversity of religious articulations. It is this diversity that raises complex religious issues, both within the internal religious community itself, and in relation to wider life such as economics, politics, ideology, science, and technology.